Invasive pneumococcal disease rates linked to meteorological factors and respiratory virus circulation (Catalonia, 2006–2012) - Ciruela, Pilar (BMC Public Health, 2016)
BACKGROUND: To study the impact of meteorological data and respiratory viral infections on invasive pneumococcal disease (IPD) rates. METHODS: We analysed all notifications of IPD and respiratory viral infections to the Microbiological Reporting System of Catalonia (2006–2012). Correlations between rates of IPD and viral infections (influenza virus, respiratory syncytial virus [RSV] and adenovirus), and meteorological variables (temperature, humidity, hours of sunshine, wind speed and number of days with rainfall) were assessed using Spearman’s correlation coefficient and negative binomial regression models. RESULTS: We found significant correlations between monthly rates of IPD and monthly rates of all respiratory viruses and meteorological factors. However, after multiple regression analysis, associations remained between IPD rates and influenza rates and reductions in temperature in the total population, and between IPD rates and adenovirus rates in children aged <5 years. When models were repeated for the total population using data from the preceding month, IPD rates increased when RSV was circulating and when the temperature was lower. In children aged <5 years, RSV circulation was associated with increased IPD rates. CONCLUSIONS: IPD rates were linked to increased activity of some respiratory viruses and reductions in temperature. Preventive measures, including influenza vaccination, may help reduce IPD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-016-3061-6) contains supplementary material, which is available to authorized users.